Tata Spasial Permukiman Kasepuhan Sinar Resmi, Kabupaten Sukabumi, Jawa Barat - Sari Mawaddahni; Lisa Dwi Wulandari; Agung Murti Nugroho (RUAS, 2021)
Kasepuhan Sinar Resmi are part of the Banten Kidul Indigenous Community with a cultural base of rice in their lives. The settlements are formed from natural, geographic, socio-economic-cultural activities that have spatial characteristics. The spatial peculiarities of the settlement are interesting things to be studied and reveal their physical and philosophical manifestations. With a qualitative descriptive analysis approach, this study aims to identify and describe the characteristics of the Kasepuhan Sinar Resmi housing based on non-physical and physical aspects. The variables studied were: 1) socio-cultural and economic, 2) public activity, 3) natural and geographic conditions, 4) spatial-forming elements of settlements, 5) physical spatial layout, and 6) building typology. The results showed that the character of the settlement was formed based on non-physical aspects in the form of consistency in carrying out the tatali paranti karuhun, as well as respect and obedience to the leaders as regulator of life in kasepuhan. This is the main factor that greatly influences the spatial layout of the Kasepuhan Sinar Resmi’s settlement physically apart from the natural and geographical conditions of the area. The implementation of respect for karuhun is the continuity of the rice culture that has been preserved until now, which is sustainable in all farming activities, and the socio-culture of the kasepuhan community.